2015
DOI: 10.1115/1.4029006
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Rotating Turbulence: A Review of Recent Experimental and Numerical Results

Abstract: Rotating turbulence is a fundamental phenomenon appearing in several geophysical and industrial applications. Its study benefited from major advances in the recent years, but also raised new questions. We review recent results for rotating turbulence, from several numerical and experimental researches, and in relation with theory and models, mostly for homogeneous flows. We observe a convergence in the statistical description of rotating turbulence from the advent of modern experimental techniques and computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 80 publications
(133 reference statements)
5
79
0
Order By: Relevance
“…Using a penalization technique the nonhomogeneous precession term d(Ω × r)/dt can be taken into account exactly [25]. Another potential source of spurious effects is due to periodic boundary conditions, which force the large-scale columns to wrap around the lattice, something that would not be possible in presence of a solid boundary [26]. The robustness of these approximations will be quantified in a study presented elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Using a penalization technique the nonhomogeneous precession term d(Ω × r)/dt can be taken into account exactly [25]. Another potential source of spurious effects is due to periodic boundary conditions, which force the large-scale columns to wrap around the lattice, something that would not be possible in presence of a solid boundary [26]. The robustness of these approximations will be quantified in a study presented elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Barker and Lithwick [19], in their local model of the elliptical instability, nonetheless showed that strong geostrophic flows emerge during the saturation and disrupt the inertial wave resonances, leading instead to growth and decay cycles. This competition between dominant geostrophic modes and inertial waves is reminiscent of the duality observed in rotating turbulence where, on one hand, geostrophic flows are widely observed [30], and on the other hand, inertial waves have been shown to survive on top of the turbulent background [31][32][33][34]. Conversely from experiments and numerical simulations of rotating turbulence, where energy is injected arbitrarily into both vortices and inertial waves through an external artificial forcing, the elliptical instability provides a natural mechanism that initially injects energy into a few inertial waves only, whose properties can be theoretically predicted.…”
mentioning
confidence: 99%
“…The two-dimensionalization and the cyclone-anticyclone asymmetry depend on the external forces and the boundary conditions (e.g., Ref. [9]). …”
mentioning
confidence: 99%